A Diversified Assembly of 1,2,4-Oxadiazol-3-amines: Metallic Thiophile Catalyzed Chemoselective One-Pot Reaction of Aryl Isothiocyanates, Amidines/Guanidines, and Hydroxylamine - Jalani, Hitesh B.; Sudarsanam, V.; Vasu, Kamala K. (Synthesis, 2012)
An efficient one-pot synthesis of 1,2,4-oxadiazol-3-amines from simple starting materials, isothiocyanates, amidines/guanidines, and hydroxylamine, is described. The reaction is facilitated by metallic-thiophile-assisted desulfurization of in situ formed amidino- or guanidinothiourea to give chemoselectively N-hydroxyguanidine intermediates that give exclusively various 1,2,4-oxadiazol-3-amines in good to excellent yields. The reaction mechanistic pathway may proceed through an intramolecular 5-exo-trig cyclization.
Keywords: 1,2,4-oxadiazol-3-amine; metallic thiophile; chemoselectivity; N-hydroxyguanidine